2019
DOI: 10.1063/1.5110287
|View full text |Cite
|
Sign up to set email alerts
|

Strong strain hardening in ultrafast melt-quenched nanocrystalline Cu: The role of fivefold twins

Abstract: Nanocrystalline and nanotwinned metals exhibit ultrahigh strength but suffer from low ductility due to the absence of the strain hardening effect. Here, we report sustained strong strain hardening up to 20% compressive strain in a melt-quenched nanocrystalline Cu structure, which contains numerous fivefold twins, stacking faults, and twin boundaries. Our molecular dynamics simulations reveal that the strong strain hardening results from the synergistic effect of constant nucleation and impedance of dislocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Nonstoichiometric titanium dioxide (TiO 2 ) has drawn broad interest due to its important role in photocatalysis, solar cells, and environmental procedures [1][2][3][4][5][6][7][8][9]. Under various experimental conditions, a broad range of O-vacancies can be formed in TiO 2 (bulk and surface), i.e., 5-10% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nonstoichiometric titanium dioxide (TiO 2 ) has drawn broad interest due to its important role in photocatalysis, solar cells, and environmental procedures [1][2][3][4][5][6][7][8][9]. Under various experimental conditions, a broad range of O-vacancies can be formed in TiO 2 (bulk and surface), i.e., 5-10% [10].…”
Section: Introductionmentioning
confidence: 99%
“…As such, twinning partials are able to cross-slip onto different constituent TBs of a penta-twin. Previous studies have shown that penta-twin core can often impede dislocations, inducing restricted migration of a TB of the penta-twin with only slight oscillation around its original location [16]. On the other hand, some simulation studies reported layer-by-layer TB migration induced by twinning partial propagation during annealing [9] or stress-relaxed [38] evolutions of penta-twins.…”
Section: Resultsmentioning
confidence: 99%
“…penta-twin with only slight oscillation around its original location [16]. On the other hand, some simulation studies reported layer-by-layer TB migration induced by twinning partial propagation during annealing [9] or stress-relaxed [38] evolutions of pentatwins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations